2015
DOI: 10.1108/hff-09-2014-0286
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady flow of variable viscosity Cu-water and Al2O3-water nanofluids in a porous pipe with buoyancy force

Abstract: Purpose – The purpose of this paper is to investigate the combined effects of buoyancy force and variable viscosity on unsteady flow and heat transfer of water-based nanofluid containing copper and alumina as nanoparticles through a porous pipe. Design/methodology/approach – Using the Boussinesq and boundary-layer approximations with Buongiorno nanofluid model. The governing nonlinear partial differential equations for the continuity, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
(21 reference statements)
0
18
0
Order By: Relevance
“…Khamis et al [55] investigated the combined effects of buoyancy force and variable viscosity on unsteady flow and heat transfer of water-based nanofluid containing copper and alumina as nanoparticles through a porous pipe, using the Boussinesq and boundary-layer approximations with Buongiorno nanofluid model. The results showed that with suction, Cu-water produces higher skin friction and heat transfer rate than Al2O3-water.…”
Section: Heat and Nanofluid Transfermentioning
confidence: 99%
“…Khamis et al [55] investigated the combined effects of buoyancy force and variable viscosity on unsteady flow and heat transfer of water-based nanofluid containing copper and alumina as nanoparticles through a porous pipe, using the Boussinesq and boundary-layer approximations with Buongiorno nanofluid model. The results showed that with suction, Cu-water produces higher skin friction and heat transfer rate than Al2O3-water.…”
Section: Heat and Nanofluid Transfermentioning
confidence: 99%
“…The effects of these parameters on the non-dimensional velocities and temperature are shown in figs. (2)- (15).…”
Section: Resultsmentioning
confidence: 99%
“…In this section, the optimal homotopy asymptotic method (OHAM) is applied to non-linear ODE (11)-(13) with the boundary conditions (14) and (15) with the following assumptions:…”
Section: Analytical Solution Using Optimal Homotopy Asymptotic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using BBD (Box-Behnken-design) code, Ghorbanian et al [20] physically optimized a corrugated-surface and porous-type cavity by nanofluid flows in the solar-radiation case. Khamis et al [21] used the approximations of boundary-layer and Boussinesq as well as the model of Buongiorno nanofluid to simulate unsteady-type flows of H2O-Cu and H2O-Al2O3 nanofluids with variable-viscosity inside a porous-type duct with buoyancy-force. Meibodi et al [22] theoretically studied the H2O-SiO2/EG performance in solar collectors by using experimental results.…”
Section: Introductionmentioning
confidence: 99%